Using Punica l. Shell Extract As A bacteriostatic For Staphylococcus aureus And Inhancing Locally Processed Sausage: Ali H. Ali , Faris A. Al-Obaidi , Meiad G. Baqir, Shahrazad M. Al-Shadeedi - Ali, Ali H. (The Iraqi Journal of Veterinary Medicine, 2007)
This study was carried out to evaluate Punica L. shell extract as abacteriostatic for Staphylococcus aureus Invitro , and select the minimaldosage to used as a food additive with species for processing locally sausageand evaluate the microbial and sensory quality .The results obtained revealedthat 0.22 % of Punica L. extract was the minimum dose has the effectivebacteriostatic for Staph. aureus Invitro and adding this percentage in mixtureof locally processed sausage significantly decreased total bacterial count andno growth of Staph. aureus were noticed . No significant differences in the